Direct detection of Brettanomyces bruxellensis in wine by PCR targeting the vinylphenol reductase gene. (January 2021) - Benito-Vazquez, Iván; Belda, Ignacio; Ruiz, Javier; Vicente, Javier; Navascués, Eva; Marquina, Domingo; Santos, Antonio
Abstract: Brettanomyces bruxellensis is among the main spoilage yeasts in wine usually found in oak barrels. As routine, laboratories at wineries use selective-differential culture media to detect this yeast. Nevertheless, it is widely recognized that other microbial species can grow on these media, getting false positive signals. In this work, we have developed a conventional PCR method based on the vinylphenol reductase gene ( VPR1 ) of B. bruxellensis applied to wines after a polyvinylpyrrolidone-based pre-treatment (7% w/v) and that allowed us to reach a low detection limit, up to 10 2 UFC/mL of wine. The procedure was conceived without time-consuming DNA extraction steps, simplifying the methodology and making it easy for applying in wineries. Highlights: Brettanomyces bruxellensis is a wine spoilage yeast due to 4-ethyphenol production. The low cellular concentration of B. bruxellensis in wines makes it hard to detect. An accurate PCR detection method to detected B. bruxellensis has been developed. The PCR procedure is designed to detect the vinylphenol reductase gene. No DNA extraction steps are needed, making the method fast and easy to apply.